Teachers’ and Students’ Perspectives on Jigsaw in EFL Classrooms: A Qualitative Study (Scripta : English Department Journal, 2026)
Cooperative learning has been widely recognized as an effective approach to supporting language learning; however, its contribution to students’ motivation and social interaction remains underexplored in many EFL contexts. This study investigates how the Jigsaw method shapes English language learning beyond academic achievement by examining teachers’ and students’ perspectives. The study was conducted at an Islamic junior secondary school in Indonesia and involved 56 eighth-grade students and three English teachers who had previously implemented the Jigsaw method in teaching descriptive texts. A qualitative descriptive approach was employed, with data collected through questionnaires, semi-structured interviews, and classroom observations. The findings indicate that the Jigsaw method created a more engaging learning environment by encouraging active participation, peer collaboration, and shared responsibility among learners. Students reported increased confidence and willingness to communicate, while teachers observed stronger classroom interaction and greater learner involvement. In addition, the method was perceived to contribute positively to students’ academic performance through collaborative knowledge construction. These findings suggest that the Jigsaw method supports meaningful EFL learning by fostering motivation and social interaction, highlighting its value as a learner-centered instructional approach in secondary school English classrooms.